Untargeted urinary metabolomics for bladder cancer biomarker screening with ultrahigh-resolution mass spectrometry - Joanna Nizioł; Krzysztof Ossoliński; Aneta Płaza-Altamer; Artur Kołodziej; Anna Ossolińska; Tadeusz Ossoliński; Anna Nieczaj; Tomasz Ruman (Scientific Reports, 2023)
Abstract Bladder cancer (BC) is a common urological malignancy with a high probability of death and recurrence. Cystoscopy is used as a routine examination for diagnosis and following patient monitoring for recurrence. Repeated costly and intrusive treatments may discourage patients from having frequent follow-up screenings. Hence, exploring novel non-invasive ways to help identify recurrent and/or primary BC is critical. In this work, 200 human urine samples were profiled using ultra-high-performance liquid chromatography and ultra-high-resolution mass spectrometry (UHPLC-UHRMS) to uncover molecular markers differentiating BC from non-cancer controls (NCs). Univariate and multivariate statistical analyses with external validation identified metabolites that distinguish BC patients from NCs disease. More detailed divisions for the stage, grade, age, and gender are also discussed. Findings indicate that monitoring urine metabolites may provide a non-invasive and more straightforward diagnostic method for identifying BC and treating recurrent diseases.